Developing a Multicultural Islamic Education Model Oriented toward Religious Moderation to Enhance Students’ Tolerance - Nabil Tito Prasetyo; Novita Eni Kartika; Chairul Anwar; Syaiful Anwar; Muhammad Idris (STIT Ahlussunnah Bukittinggi, 2026)
This study aims to describe the implementation of a multicultural Islamic education model oriented toward religious moderation in improving students’ tolerance attitudes at Islamic junior high schools. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving the principal, Islamic Education teachers, and students selected through purposive sampling. The validity of the data was ensured through source and technique triangulation, while the data were analyzed thematically through data reduction, data display, and conclusion drawing. The findings revealed that the implementation of multicultural Islamic education oriented toward religious moderation was able to enhance students’ tolerance attitudes, as reflected in mutual respect, appreciation of differences, and inclusive social interactions within the madrasah environment. The implementation model was carried out through the integration of multicultural values into the learning process, school culture, and students’ religious activities. In addition, the role of teachers as facilitators, support from madrasah policies, and the strengthening of a religious moderation-based curriculum became the main factors contributing to the successful implementation of the model. The implications of this study indicate that multicultural Islamic education can serve as an effective strategy for strengthening religious moderation and fostering a sustainable culture of tolerance within Islamic educational institutions.